Concept of revitalization of selected military facilities of dragoons barracks in Olsztyn = Koncepcja rewitalizacji wybranych obiektów powojskowych zespołu Koszar Dragonów w Olsztynie - Zagroba, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Revitalization is a complex program to restore the functioning of the neglected urban areas in terms of spatial, economic and social. Revitalization activities on post-military facilities are stopping negative phenomena, such as degradation of space, social pathology or lack of proper functioning of the area, adapted to modern needs. The object of the work is to present some aspects with the revitalization of former military facilities in the area of the Artyleryjska Street in Olsztyn.
Keywords: obiekty powojskowe; koszary dragonów; rewitalizacja; urbanistyka; military facilities; dragoons barracks; revitalisation; regeneration; urban planning